Structure/Function analysis of the Staphylococcus aureus extracellular adherence protein and the human innate immune system - Woehl, Jordan Lee (Kansas State University, 2017)
The pathogenic bacterium Staphylococcus aureus actively evades many aspects of human innate immunity by expressing a series of secreted inhibitory proteins. A number of these proteins have been shown to specifically bind to and inhibit components of the complement system. Since complement is known to play a significant role in the pathophysiology of human inflammatory diseases, our long-term goal is to understand the structure, function, and mechanism of Staphylococcal immune evasion proteins to develop complement-targeted therapeutics. Since its discovery, the extracellular adherence protein (Eap) has been shown to be a crucial component in the pathogenesis and survival of S. aureus through its ability to interact and inhibit multiple aspects of the innate immune system. We have shown that Eap inhibits the classical and lectin pathways of complement by a previously undescribed mechanism. Specifically, Eap binds with nanomolar affinity to complement protein C4b, and thereby blocks binding of the classical and lectin pathway pro-protease C2 to C4b. This effectively eliminates formation of the CP/LP C3 proconvertase, which is required for amplification of downstream complement activity and subsequent inflammatory events. The full-length, mature Eap protein from S. aureus strain Mu50 consists of four ~97 residue domains, each of which adopt a similar beta-grasp fold, and are connected to one another through short linker regions that give rise to an elongated, but structured protein. Through multiple structural and functional assays, we have identified the 3rd and 4th domains of Eap as being critical for interacting with C4b and subsequent inhibition of the complement cascade. Alternative approaches to a standard co-crystal structure of Eap34 bound to C4b provided evidence that Eap domains 3 and 4 both contain a low affinity, but saturable binding site for C4b; we were able to map these sites to the α-chain and γ-chain, specifically the metal-ion-dependent adhesion site of the C345c domain, of C4b, both of which have been previously shown to be required for pro-protease binding. To provide higher resolution information, we took advantage of the abundance of surface exposed lysines in Eap34, and employed a lysine-acetylation foot printing mass spectrometry technique. This identified seven lysines in Eap34 that undergo changes in solvent exposure upon C4b binding and confirmation of these residues was done through site-directed mutagenesis, followed by direct binding and functional assays. Together, these results provide structural and functional insight into one of the many ways that Staphylococcus aureus can evade the killing powers of the innate immune system. Future plans are directed at conducting site-specific screens to identify small molecule/peptide compounds that target the Eap34 binding site on C4b. Such molecules would constitute attractive lead compounds in the search for specific inhibitors of the classical and lectin complement pathways.
Keywords: Complement system; Staphylococcus aureus; Extracellular adherence protein; Structural biology; Immunology